Solar-driven absorption cycle for space heating and cooling. (5th March 2020) - Vallès, Manel; Bourouis, Mahmoud; Boer, Dieter
Highlights: Two operational modes of an absorption cycle are proposed for solar heating and cooling. Ammonia-Lithium nitrate is used as a working pair. In cooling mode the system operates as a single-stage absorption cycle. In heating mode the system operates as a single-stage heat transformer. Heat and mass exchangers in both cycles are the same, only internal flow direction changes. Abstract: The Energy Performance of Buildings Directive (EPBD) requires that all new buildings in the European Union be nearly zero energy buildings (NZEB) by the end of 2020. Consequently, energy saving measures must be introduced in the design phase. However, in most cases there will still be a cooling and heating demand, which could be satisfied using renewable energy. Of all of the renewable energy resources, solar energy has been given most attention since it is CO2 neutral. The present study investigates a new solar thermally-driven system that meets the heating and cooling demands of buildings. This system consists of a reversible absorption cycle, which operates as a single-effect absorption cycle in the cooling mode and as a heat transformer in the heating mode. The components of both cycles are the same, and only the flow direction inside the system changes. The working pair selected was ammonia-lithium nitrate so no rectifier is required and there are no problems of refrigerant freezing at low condensing temperatures when the cycle operates as a heat transformer. For both cycles, a mathematical model is developed to obtain feasible driving temperatures and evaluate the cycle's coefficient of performance (COP) depending on the ambient temperature. The results show that in the heating mode, the heat transformer cycle can be driven with a heat source at 40 °C to produce hot water at 55 °C at an ambient temperature of 0 °C and a COP of about 0.45. In addition, the lower the ambient temperature, the higher the hot water temperature that the heat transformer can produce. In the cooling mode, the single-effect absorption cycle can be driven with a heat source at 85 °C to produce chilled water at 7 °C at an ambient temperature of 30 °C and a COP of 0.6. As a result, this configuration overcomes the limitations of existing absorption cycles and presents an interesting alternative to existing heating and cooling systems.